2019
DOI: 10.1111/ijfs.14431
|View full text |Cite
|
Sign up to set email alerts
|

An overview of papaya seed oil extraction methods

Abstract: Summary Papaya seeds account for about 20% of the total fresh fruit weight. The seeds are generally discarded as agricultural waste products during fruit processing despite being edible. The seeds contain high levels of lipid and thus can be a new source of edible oil. Numerous technologies have been used for extraction of crude oil from papaya seeds. Papaya seed oil is composed mostly of unsaturated fatty acids with oleic acid being the major one. The oil also contains lipophilic phytochemicals such as tocoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Furthermore, oleic acid (18:1) in MUFA and linoleic acid (C18:2, n-6) in PUFA were the main components in the extracted oil, which are mostly in agreement with the findings of Tangsanthatkun et al [ 19 ] and Tan [ 52 ]. Furthermore, a literature comparison exhibits the oleic acid (18:1) of the extracted oil is in agreement with avocado oil's oleic acid (30–61%) [ 46 , 52 ] but, lower than papaya seed oil (70–78%) [ 53 ]. However, the different ratios of the fatty acid composition may be due to the variations in extraction processes and factors, such as the origin of species, maturation stage, sex, season, and geographical regions, as observed in previous studies [ 11 , 14 ].…”
Section: Resultsmentioning
confidence: 53%
“…Furthermore, oleic acid (18:1) in MUFA and linoleic acid (C18:2, n-6) in PUFA were the main components in the extracted oil, which are mostly in agreement with the findings of Tangsanthatkun et al [ 19 ] and Tan [ 52 ]. Furthermore, a literature comparison exhibits the oleic acid (18:1) of the extracted oil is in agreement with avocado oil's oleic acid (30–61%) [ 46 , 52 ] but, lower than papaya seed oil (70–78%) [ 53 ]. However, the different ratios of the fatty acid composition may be due to the variations in extraction processes and factors, such as the origin of species, maturation stage, sex, season, and geographical regions, as observed in previous studies [ 11 , 14 ].…”
Section: Resultsmentioning
confidence: 53%
“…Seeds from fruit and vegetable processing have been extensively studied by researchers due to their high content in oil and bioactive compounds. Likewise, papaya seeds (a by‐product of the fruit industry) are a rich source of oil, proteins, and dietary fibers (Tan, Tan, & Tan, 2020). Papaya seed can yield up to 30%–34% oil, which contains monounsaturated fatty acids and antioxidants.…”
Section: Uae Impact On the Quality Of Oil From Fruit Seedsmentioning
confidence: 99%
“…Nonetheless, this procedure also needs to include a separation stage after the extraction to segregate the residues from the compounds of interest, and the increased temperature applied during the process could damage thermolabile compounds (Gomez et al, 2020). Lastly, despite mostly being applied laboratory-scale involving an expensive equipment installation (Tan et al, 2020), and the need of stages of purification after the extraction procedure of bioactive compounds (Rodr ıguez-Ruiz et al, 2022), PLE has demonstrated to be a fast eco-friendly technique that produces high EYs of medium and high polarity compounds from solid matrices (Rodr ıguez-Ruiz et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…, 2016). However, it has been used at a laboratory scale, leaving behind its applicability in the food industry and the economic cost of the process (Tan et al. , 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation